2016
DOI: 10.3233/wor-162293
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the potential benefits of using a backpack with non-flexible straps

Abstract: Backpacks cause some bad effects on kinematics of gait. In this study, by testing modified backpacks, some improvements were seen, specifically in posture, which may be useful to reduce side effects of backpack carrying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In addition, it was reported that a traditional double-strap BP can induce different effects on trunk posture depending on the design of the straps: non-flexible straps caused a non-significant forward tilt of the trunk during gait with respect to the unloaded condition, while traditional straps did so when loaded up to 10% BM, suggesting that the formers as optimal [ 33 ]. It was found that the torso angle in the sagittal plane at a load of 15–25% BM was significantly different when worn with a TP compared to BP, with the former allowing a posture closer to the unloaded condition [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was reported that a traditional double-strap BP can induce different effects on trunk posture depending on the design of the straps: non-flexible straps caused a non-significant forward tilt of the trunk during gait with respect to the unloaded condition, while traditional straps did so when loaded up to 10% BM, suggesting that the formers as optimal [ 33 ]. It was found that the torso angle in the sagittal plane at a load of 15–25% BM was significantly different when worn with a TP compared to BP, with the former allowing a posture closer to the unloaded condition [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…To optimize the interaction with the pack, the use of a hip belt, and non-flexible, shorter shoulder straps would be beneficial in terms of both kinematics and comfort, as well as a more vertical load distribution [ 27 , 32 , 33 , 68 ]. Furthermore, in children, it is desirable not to exceed 10% BM considering the total load.…”
Section: Discussionmentioning
confidence: 99%
“…Backpacks are among the most popular load carriers in the world and are used by millions of people in everyday professional or sporting activities 1 . Especially in the field of sports, the key factors of comfort, functionality and fit of backpacks are of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize the effects of carrying heavy backpacks, several models of bags have been proposed. Some of the proposals promote a more upright posture by carrying the load in big pockets at the hip level [31] or replacing the flexible shoulder straps by rigid ones [31]. Interior pockets have also been developed for school backpacks to distribute the weight.…”
Section: Introductionmentioning
confidence: 99%